Short Communication: RAPD fingerprinting key and phylogenetic of nine seagrass species from Sanur coastal water, Bali, Indonesia using matK sequences - MADE PHARMAWATI; UUL SHOVI NURKAMILA; STEVANUS STEVANUS (Society for Indonesian Biodiversity, 2016)
Pharmawati M, Nurkamila US, Stevanus. 2016. RAPD fingerprinting key and phylogenetic of nine seagrass species from Sanur coastal water, Bali, Indonesia using matK sequence. Biodiversitas 17: 687-693. In Bali, there are nine species of seagrass identified based on morphological characteristics. Development of molecular markers assist identificaton and evolutionary studies of many species including seagrass species. This study aimed to develop a fingerprinting key of nine seagrass species found at Sanur (Sanur Beach and Sindhu Beach), Bali, based on RAPD markers and to analyse their phylogenetic relationships using the matK region. Seagrass samples were collected at low tide and DNA was extracted using CTAB buffer. Six RAPD primers were used in the study. Sequences of matK were analyzed using MEGA 5.2. The phylogenetic tree was constructed by Maximum Likelihood method with 1000 bootstrap replicates. Based on RAPD banding pattern, a DNA fingerprinting key was successfully developed using only one primer — OPB12. Phylogenetic analysis of matK sequences grouped seagrass species by genera. There were five clades identified and the tree recognised that Cymodoceaceae was paraphyletic. This result is in disagreement with a previous study using combined rbcL and matK sequences which discussed the monophyly of Cymodoceaceae. Recent published paper using ITS sequence showed that cymodoceaceae might not be monophyletic group. This result supported our finding that Cymodoceaceae is not in the monophyletic group. Combined DNA sequences of chloroplast, nuclear and published paper using ITS sequencing showed that Cymodoceaceae mitochondrial DNA will further resolve phylogeny of seagrass species.